2021
DOI: 10.1177/1357633x20986038
|View full text |Cite
|
Sign up to set email alerts
|

Changing attitudes towards teletherapy in Austrian therapists during the COVID-19 pandemic

Abstract: Introduction Telehealth and its usage strongly depend on regulatory frameworks and user acceptance. During the COVID-19 pandemic, physiotherapists, occupational therapists, speech-language therapists and their patients experienced restrictions regarding the usual face-to-face therapy. Teletherapy has become a highly discussed medium for providing therapy services. This study aimed at assessing Austrian therapists’ attitudes towards teletherapy, including perceived barriers, during and before the COVID-19 lockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 26 publications
1
32
0
2
Order By: Relevance
“…The major issue was related to problems with patients' compliance, given the lack of physical contact between therapists and their patients. This study showed that the impersonality of care seems to be the biggest barrier for the implementation of telehealth systems, similar to findings reported in a study by Rettinger et al [15]. Another issue for the SLTs who delivered TR treatments during the lockdown was related to internet connection problems, which made treatments more difficult to provide, and negatively influenced the feasibility evaluation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The major issue was related to problems with patients' compliance, given the lack of physical contact between therapists and their patients. This study showed that the impersonality of care seems to be the biggest barrier for the implementation of telehealth systems, similar to findings reported in a study by Rettinger et al [15]. Another issue for the SLTs who delivered TR treatments during the lockdown was related to internet connection problems, which made treatments more difficult to provide, and negatively influenced the feasibility evaluation.…”
Section: Discussionsupporting
confidence: 83%
“…Authors found that therapists perceived the lack of professional training as a barrier to the implementation of teletherapy intervention, as well as a certain impersonality of care. Nearly half of the surveyed therapists reported that teletherapy is impersonal, and more than a half agreed that they urgently needed physical contact with their patients [15]. Indeed, clinicians' perspectives and opinions could differ from the results of previous research studies, mainly due to technology-specific issues and resistance to change from therapists [16].…”
Section: Introductionmentioning
confidence: 95%
“…In terms of age, gender and work specialization distribution, the sample of participants was similar to previous studies conducted in Austria [23,55]. The official registry of Austrian physiotherapists lists around 16,000 persons, half of them being self-employed therapists [34].…”
Section: Limitationsmentioning
confidence: 87%
“…Another limitation is that the survey was accessible only online, which may exclude physiotherapists with lower technical affinity. In terms of gender, age and work specialization, the sample of respondents was similar to previous studies in Austria [60,61]. Due to the online setting, the study limitations also include the absence of a researcher.…”
Section: Discussionmentioning
confidence: 99%